Effects of prenatal yoga exercise on hepcidin and ferritin levels in pregnant women - Farida Tandi Bara; Suryani As'ad; Irfan Idris; Deviana Soraya Riu; Mardiana Ahmad (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.